Interest Rate Pass-Through in the Dominican Republic - Grigoli, Francesco (IMF Working Papers; Working Paper ;, 2015)
A well-functioning monetary transmission mechanism is critical for monetary policy. As the Dominican Republic recently adopted an inflation targeting regime, it is even more relevant to guarantee that changes in the monetary policy rates are quickly and fully reflected in retail rates, to eventually influence aggregate demand and inflation. This paper estimates the interest rate pass-through of the monetary policy rate to retail rates and explores asymmetries in the adjustment. We find evidence of complete pass-through to retail rates, confirming the effectiveness of the monetary policy transmission mechanism. However, our results also suggest a faster pass-through to lending rates than to deposit rates and asymmetric adjustments of short-term rates, as deposit rates respond faster to policy rate cuts and lending rates respond faster to policy rate hikes. Measures to enhance competition in the financial system could help to achieve a symmetric adjustment of retail rates.